2018
DOI: 10.2105/ajph.2018.304645
|View full text |Cite
|
Sign up to set email alerts
|

“Spanish Flu”: When Infectious Disease Names Blur Origins and Stigmatize Those Infected

Abstract: Despite not originating in Spain, the 1918 influenza pandemic is commonly known as the “Spanish flu”—a name that reflects a tendency in public health history to associate new infectious diseases with foreign nationals and foreign countries. Intentional or not, an effect of this naming convention is to communicate a causal relationship between foreign populations and the spread of infectious disease, potentially promoting irrational fear and stigma. I address two relevant issues to help contextualize these nam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 14 publications
2
38
0
4
Order By: Relevance
“…Similarly, some news sources and officials have devoted considerable time to criticizing Chinese cultural practices or otherwise blaming China for the outbreak (Chiu, 2020). Numerous criticisms have been raised regarding this type of framing because of its potential to fuel prejudice and encourage discriminatory behaviors (Hoppe, 2018). The social cognition perspective summarized above aligns with these criticisms, underscoring how framing and repeated messaging that stigmatizes China can inform attitudes and social judgments.…”
Section: Media Institutions and Covid-prejudicementioning
confidence: 94%
“…Similarly, some news sources and officials have devoted considerable time to criticizing Chinese cultural practices or otherwise blaming China for the outbreak (Chiu, 2020). Numerous criticisms have been raised regarding this type of framing because of its potential to fuel prejudice and encourage discriminatory behaviors (Hoppe, 2018). The social cognition perspective summarized above aligns with these criticisms, underscoring how framing and repeated messaging that stigmatizes China can inform attitudes and social judgments.…”
Section: Media Institutions and Covid-prejudicementioning
confidence: 94%
“…Indeed, evidence of pandemics triggering bias dates back at least to the 1918 influenza outbreak. Despite not originating in Spain, the virus became known as the “Spanish flu” which led to stigmatization of Spanish nationals (Hoppe 2018 ). Similarly, there was an outbreak of the bubonic plague in India in 1994 and, despite being localized to one region, the stigma of the disease led to many countries banning travel and imports from the entire nation (Barrett and Brown 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on stigma related to infectious diseases have revealed that it is not only individual patients who face stigma from infectious diseases, but can also be entire racial or ethnic groups who have or are perceived as having a higher likelihood of being infected [22]. Wuhan, the capital of Hubei Province, was the most severely affected area during the COVID-19 epidemic in China.…”
Section: Introductionmentioning
confidence: 99%